The Effect of Material Incentives in Effectiveness of Work Teams A Field Study in the Scientific Agricultural Research Center in Lattakia - ونوس عبود; كندة علي ديب; جميل عيسى (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The aim of the research is to determine the effect of material incentives in the effectiveness of work teams (team performance, team member satisfaction, team viability) at the Scientific Agricultural Research Center in Lattakia. The researcher relied on the descriptive analytical method as a general approach to research. A questionnaire was designed and distributed to a sample of members of the work teams at the Center for Scientific Agricultural Research in Lattakia. The number of members of the work teams reached 185, the number of valid questionnaire for statistical analysis was 181 responses. The researcher used the statistical program (SPSS) in conducting statistical and hypothesis testing. The research reached several results, the most important is: There is a positive significant effect for material incentives in the effectiveness of work teams in their dimensions (team performance, team member satisfaction, team viability) in the Scientific Agricultural Research Center in Lattakia.